Hommage à Vann Nath = Vann Nath tribute = Phakdey chom paus Vann Nath/ . Vann Nath tribute (Cercle des Amis de Vann Nath, 2013)
Catalogue published for the exhibition in Bophana Center, Phnom Penh, 12 January - 12 February 2013. Covertitle: Vann Nath tribute = Vann Nath hommage